Religious Reforms in Uzbekistan and its Impact on Society (Eurasian Journal of Humanities and Social Sciences, 2022)
This article provides information about the reforms being carried out in the field of religion in Uzbekistan and its impact on society. Also, the measures implemented in our country for religious tolerance and inter-ethnic harmony are reflected in the article.